Total Hip Arthroplasty for the Sequelae of Legg-Calvé-Perthes Disease - Baghdadi, Yaser M. K. (Springer US, 2013)
BACKGROUND: The durability and risks associated with total hip arthroplasty (THA) for patients with a history of Legg-Calvé-Perthes disease (LCPD) are not well known. QUESTIONS/PURPOSE: We sought to (1) determine the survivorship of THAs performed for LCPD; (2) assess hip scores and complications associated with THA in this patient population; and (3) compare results between patients who had undergone surgery in childhood with patients who had conservative treatment. METHODS: We reviewed 99 primary THAs performed in 95 patients with a history of LCPD with minimum 2-year followup (mean ± SD, 8 ± 5 years). Mean age at THA was 48 ± 15 years. RESULTS: A total of 10 revisions were performed. Using revision for any reason as the end point, the 8-year survival rate was 90% (95% confidence interval [CI], 76%–96%) for cementless implants compared with 86% (95% CI, 57%–96%) for hybrid implants. The mean Harris hip score improved by 31 ± 16 (n = 76). Complications occurred in 16% of hips. The most common major complication was intraoperative fracture (eight femoral, one acetabular). Three patients developed sciatic nerve palsy after a mean lengthening of 2.2 ± 1 cm compared with a mean of 1.4 ± 1 cm in patients with intact sciatic nerve (p = 0.3). CONCLUSIONS: Cementless THAs for the sequelae of LCPD demonstrate 90% survival from any revision at 8 years followup. THAs for the sequelae of LCPD can be complicated and technically difficult. Intraoperative fractures and nerve injuries are common. Care should be taken to avoid excessive limb lengthening. LEVEL OF EVIDENCE: Level IV, retrospective case series. See Guidelines for Authors for a complete description of levels of evidence.